Clinical feasibility of Axillary Reverse Mapping and its influence on breast cancer related lymphedema: a systematic review. (May 2016) - Gebruers, Nick; Tjalma, Wiebren A.A.
Abstract: Breast cancer is the most common malignancy in women worldwide. Fortunately, the overall survival is good. Therefore it is important to focus on the morbidities related to breast cancer treatment. One of the most dreaded morbidities is lymphedema. In 2007 the Axillary Reverse Mapping (ARM) was introduced to limit the invasiveness in the axilla during breast cancer surgery. It is hypothesized that ARM is able to limit the incidence of breast cancer related lymphedema (BCRL) considerably. This systematic review aims to answer the following research questions: (1) which approaches for ARM are described? (2) Is ARM surgical feasible and oncological safe? (3) Does ARM decrease the incidence of lymphedema after sentinel lymph node biopsy (SLNB) and axillary lymph node dissection (ALND)? In total 27 papers were retrieved using four electronic databases (PubMed, Web of Science, Medline and Cochrane clinical trials; assessed until May 13, 2015. The level of evidence of these studies was low (mostly level 3). Therefore the conclusions are that the ARM procedure is feasible although ARM-node rates have a broad range. Additionally, from a theoretical point there is a clear benefit from ARM in terms of lymphedema prevention. From a practical point there is little scientific data to support this due to the lack of studies; and especially because of the different methods and definitions for lymphedema used in the different studies.